Dampak Negatif Perusakan Hutan Sebagai Sumber Inspirasi Penciptaan Karya Semi Lukis - -, Yulianto (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
The negative impact of forest destruction in nature giving out a deep meaning for the author. One thing that is of concern and disquiet the author is able to provide a source of inspiration in the creation of the work. The exploration process makes an inspiring turn into something even more special is the theme of creation. The theme of this study of the of art is the impact of forest destruction. Background and a strong visual concept could produce visual elements according to the style1Â personal authors, ranging from lines, colors, and forms a new metaphor. Deliberately and non deliberately during the process of creation is sometimes able to provide an interesting shape or composition that has not been thought about at the beginning of the work of art (sketches). In the creation of the work, the author tries to create some of the works in the form of works of art in the style and shape according to the character and aesthetic achievement that is owned by the author.Keywords: natural, experimentation, painting